Syncretism of myth and ratio (following the example of early Greek philosophy) - Бова, В. В.; Bova, V. V.; Левченко, Леся Юріївна; Levchenko, L. Yu.; Levchenko, Lesia Yu.; Левченко Л. Ю. (Одеса, 2021)
The article is an attempt at a philosophical reflection on the problems of the universe in ancient Greece. An analysis of the teachings of the Milesian school (Thales, Anaximenes, Anaximander), Heraclitus, Anaxagoras, Xenophanes, Pythagoras show the relationship between the cosmological and mythological worldview. These philosophers tried to find answers to cosmological questions: the origin of the universe, its arche, what is the need for its existence, the cause, and purpose, what is its structure. In the language of Thales, Anaximenes, Anaximander, and Heraclitus, mythopoetic is clearly traced to explain the arche of the existence and structure of the Cosmos. Xenophanes is considered the first to sarcastically approach the belief in Greek gods and mythical stories about them, and the root cause of it is the only god. The worldviews of the ancient Greek philosophers about nature, God, and man can be interpreted as being on the verge of contradictions between mythology and philosophy. Philosophy is comprehended as a synthesis of metaphysical and religious cosmology. Cosmology operates with such universal categories as Cosmos, time, and phenomena. Unlike modern cosmological scientific reflections on the universe, the ancient Greeks sought to solve the problems of creation and the laws of the world through the syncretism of philosophy and mythology. The philosophers of ancient Greece simultaneously used a combination of the dialectical method of philosophizing with myth to find answers to the basic questions posed by cosmological science. And this means: what is the origin of the universe, what is its root cause, what is the need for its existence, cause or purpose, what are its components. The article aims to show the syncretism of two antagonistic ways of thinking: mythological and rational, at the stage of the origin of philosophy in ancient Greece. Examples of the early Greek philosophers’ views show the formation of ideas about the world (space) and a man on the verge of contradictions between the mythological and religious worldview. The first part of the study considers the myth as a way to comprehend reality, the second – the presence of the mythological in the early Western philosophical cosmocentric paradigm. To show how to combine the dialectical method of philosophizing with myth to find answers to basic worldview questions, we turned to the views of the Miletus, Pythagoreans and Heraclitus, Xenophanes. In the language of Thales, Anaximenes, Anaximander, and Heraclitus mythopoetic is traced to explain the arche of the existence and structure of the Cosmos.

Стаття є спробою філософської рефлексії проблем світобудови у Стародавній Греції. На прикладі вчень представників мілетської школи (Фалеса, Анаксімена, Анаксимандра), Геракліта, Анаксагора, Ксенофана, Піфагора показано взаємозв’язок космологічного та міфологічного світоглядів у процесі пошуку відповідей на світоглядні питання: походження Всесвіту, його першопричини, у чому проявляється необхідність його існування, причини та цілі, його структури. У мові Фалеса, Анаксімена, Анаксимандра та Геракліта чітко простежується міфопоетика для пояснення першопричин буття та структури космосу, а Ксенофан був першим, хто саркастично підходив до віри у грецьких богів і міфічні оповіді про них, а також першим, хто вважав першопричиною єдиного бога. Світоглядні уявлення давньогрецьких філософів про природу, Бога та людину можна трактувати як такі, що перебувають на межі суперечностей між міфологією та філософією, а їхню філософію – як синтез метафізичної та релігійної космології. Космологія оперує такими універсальними категоріями, як Космос, час і явища. На відміну від сучасних космологічних наукових роздумів про Всесвіт, стародавні греки прагнули вирішити проблеми творіння та закони світу за допомогою синкретизму філософії та міфології. Стаття має на меті показати синкретизм двох антагоністичних способів мислення – міфологічного та раціонального – на етапі зародження філософії у Стародавній Греції. Приклади поглядів ранніх грецьких філософів свідчать про формування уявлень про світ (космос) і людину на межі суперечностей між міфологічним і релігійним світоглядом. Перша частина дослідження розглядає міф як спосіб осягнення дійсності, друга – наявність міфологічного у ранньозахідній філософській космоцентричній парадигмі. Щоб показати, як поєднати діалектичний метод філософствування з міфом, щоб знайти відповіді на основні світоглядні питання, ми звернулися до поглядів Мілета, Піфагора, Геракліта, Ксенофана. У мові Фалеса, Анаксимена, Анаксимандра та Геракліта простежується міфопоетика для пояснення архе існування та будови Космосу.
Bova V. V. Syncretism of myth and ratio (following the example of early Greek philosophy) / V. V. Bova, L. Yu. Levchenko // Актуальні проблеми філософії та соціології : Науково-практичний журнал / Голов. ред. С. Г. Секундант, відпов. ред. Д. В. Яковлев ; Міністерство освіти і науки України ; Національний університет "Одеська юридична академія". - Одеса, 2021. - Вип. 30. - С. 9-17.
Keywords: myth; rational thinking; worldview; Early Greek philosophy; Cosmos; universe; arche; міф; раціональне мислення; світогляд; ранньогрецька філософія; Космос; Всесвіт; Архе; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::Philosophy subjects